Effectiveness of oxytocin massage for breast milk production: a literature review - Ni Luh Linda Ayuni Tania; Titih Huriah (Universitas Aisyah Pringsewu, 2023)
Riskesdas data in 2021 shows that only 52.5% or half of 2.3 million of 1-6 month babies in Indonesia who get exclusive breastfeeding. Most provinces still has low percentage of exclusive breastfeed and under the national average. One of the factors is due to the unhealthy condition of the mother and due to the lack of confidence when giving exclusive breastfeeding. Giving therapy massage that combines oxytocin with other therapies becomes a specialized intervention to assist mothers in producing exclusively breast milk. This literature reviews aimed to know the effectiveness of Oxytocin Massage for increasing Milk production. The literature review employed PRISMA method. The database used Scopus, PubMed, Science Direct, EBSCO, PROQUEST, NILITI, and Google Scholar. The key words were included Mother AND Oxytocin OR massage Oxytocin AND Breast milk AND RCT. The inclusion criteria used were RCT articles 2017 to 2022, using English and Indonesian, full text and the exclusion criteria such as reviewed, unoriginal publications including a letter to the editor, abstracts only, and books. An assessment tool of critical JBI was used to evaluate the quality of journal. The result showed that the Oxytocin Massage with or without a combination of other therapies can help mothers to have an exclusive breast milk production.Abstrak: Data Riskesdas tahun 2021 menunjukkan hanya 52,5% atau separuh dari 2,3 juta bayi 1-6 bulan di Indonesia yang mendapatkan ASI eksklusif. Sebagian besar provinsi masih memiliki persentase ASI eksklusif yang rendah dan di bawah rata-rata nasional. Salah satu faktornya adalah karena kondisi ibu yang tidak sehat dan kurang percaya diri saat memberikan ASI eksklusif. Pemberian terapi pijat yang mengkombinasikan oksitosin dengan terapi lain menjadi intervensi spesialis untuk membantu ibu dalam produksi ASI eksklusif. Tinjauan pustaka ini bertujuan untuk mengetahui efektivitas Pijat Oksitosin untuk meningkatkan produksi ASI. Tinjauan literatur menggunakan metode PRISMA. Basis data menggunakan Scopus, PubMed, Science Direct, EBSCO, PROQUEST, NILITI, dan Google Scholar. Kata kuncinya termasuk Ibu DAN Oksitosin ATAU Pijat Oksitosin DAN ASI DAN RCT. Kriteria inklusi yang digunakan adalah artikel RCT 2017 hingga 2022, menggunakan bahasa Inggris dan Indonesia, teks lengkap dan kriteria eksklusi seperti ulasan, publikasi tidak asli termasuk surat kepada editor, abstrak saja, dan buku. Alat penilaian JBI kritis digunakan untuk menilai kualitas jurnal. Hasil penelitian menunjukkan bahwa Pijat Oksitosin dengan atau tanpa kombinasi terapi lain dapat membantu ibu untuk menghasilkan ASI eksklusif.